Surveying business uncertainty - David Altig; Jose Maria Barrero; Nicholas Bloom; Steven J. Davis; Brent Meyer; Nicholas Parker (Federal Reserve Bank of Atlanta, 2019)
We develop a new monthly panel survey of business executives and a new question design that elicits subjective probability distributions over own-firm outcomes at a one-year lookahead horizon. Our Survey of Business Uncertainty (SBU) began in 2014 and now covers 1,500 firms drawn from all 50 states, every major industry in the nonfarm private sector, and a full range of firm sizes. We use SBU data to measure expected future outcomes for the growth of sales, employment, and investment for each firm and the uncertainty surrounding those expectations. Mean expectations are highly predictive of realized growth rates in the firm-level data, and subjective uncertainty is highly predictive of absolute forecast errors. We also use the SBU data to produce a Business Expectations Index (first moment) and a Business Uncertainty Index (second moment) for the U.S. economy. In Granger causality tests, the Business Expectations Index has statistically significant predictive power for a range of prominent business cycle indicators. The SBU also includes special questions that elicit additional information, including the perceived effects of specific government policy developments on the firm's decisions and outcomes.
Keywords: L2; M2; O32; O33; 330; business uncertainty; subjective forecast distributions; surveys